Digital government principles and best practices - Pavlichev, Alexei; Garson, G. David; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2004)
E-government has emerged not merely as a specialization in public administration but as a transformative force affecting all levels and functions in government. This publication, written by a collection of practitioners and researchers, provides an overview of the management challenges and issues involved in seeking a new form of governance--digital government.
The promise of digital government -- A brief history of the emergence of digital government in the United States -- The emergence of digital government: international perspectives -- Portals and policy: implications of electronic access to U.S. federal government information and services -- Government web portals: management issues and the approaches of five states -- The organizational culture of digital government: technology, accountability & shared governance -- Political implications of digital (e-) government -- Consequences of the cyberstate: the political implications of digital government in international context -- Digital government and individual privacy -- E-procurement: state government learns from the private sector -- Issues in e-commerce and e-government service delivery -- Digital government and criminal justice -- Digital government: balancing risk and reward through public/private partnerships -- Ethics and digital government -- Data warehousing and the organization of governmental databases -- Digital government and geographic information systems -- Training for digital government -- The e-government challenge for public administration education -- Digital government and the digital divide -- Digital government and citizen participation in the United States -- Digital government and citizen participation in international context -- The future of digital government.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on May 25, 2010).
Keywords: Internet in public administration -- United States; Electronic books